Analysis of utilization, quality and costs of maternal and child health clinic services. - Jayatissa, K.L.R (My University, 1997)
A descriptive study was carried out to determine the pattern of utilization, unit costs and the quality of services provided through the different types of clinics in a divisional director of health services(DDHS) area. There were no differences in the quality of care between different types of clinics, when data from clinic observations, examination of records and interviews with recipients of the services were studied. However, several areas where improvements could be made were identified, many of them could be achieved with minimum costs with improved managerial efforts(e.g. improving supervision, implementing a client flow system in the clinics) Such interventions could have a positive influence on the quality of care and on costs. This study also identified that useful information can be obtained on quality of services by developing simple tools(e.g. check-list) and using them for periodic review. In order to gain improvements in the health status of mothers and young children, it is necessary to improve the quality of services. The additional resources needed for such improvements are minimum. Inter relationships between utilization, cost of services and quality has to be considered for relevant changes.